2016
DOI: 10.3390/su8090959
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Level Rise and Land Subsidence: Impacts on Flood Projections for the Mekong Delta’s Largest City

Abstract: Abstract:The present paper demonstrates that inundation levels in the Mekong Delta's largest city, Can Tho, are predominantly determined by ocean tides, sea-level rise, and land subsidence. Our analysis of inundation patterns projects that the duration of inundation at an important road in the city will continue to rise from the current total of 72 inundated days per year to 270 days by 2030 and 365 days by 2050. This is attributed to the combined influence of sea-level rise and land subsidence, which causes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…Entre terre et eaux, le delta du Mékong Avec 55 000 km², le delta du Mékong est un des mégadeltas asiatiques (figure 4.14) : 18 millions de personnes y vivent (330 habitants/km², 20 % de la population du Vietnam), notamment en cultivant 7,5 millions d'hectares de terres formées par les alluvions du fleuve accumulées depuis plus de 6 000 ans (Takagi et al, 2016). Bien que limitrophe de la mégapole de Ho Chi Minh Ville 17 , le delta du Mékong ne contribue qu'à moins de 10 % de la production industrielle du pays.…”
Section: La Plaine Inondable Du Tonlé Sap Au Cambodgeunclassified
See 1 more Smart Citation
“…Entre terre et eaux, le delta du Mékong Avec 55 000 km², le delta du Mékong est un des mégadeltas asiatiques (figure 4.14) : 18 millions de personnes y vivent (330 habitants/km², 20 % de la population du Vietnam), notamment en cultivant 7,5 millions d'hectares de terres formées par les alluvions du fleuve accumulées depuis plus de 6 000 ans (Takagi et al, 2016). Bien que limitrophe de la mégapole de Ho Chi Minh Ville 17 , le delta du Mékong ne contribue qu'à moins de 10 % de la production industrielle du pays.…”
Section: La Plaine Inondable Du Tonlé Sap Au Cambodgeunclassified
“…Avec un rabattement de l'aquifère pouvant atteindre 70 cm/an 29 , la subsidence induite en surface varie de 1,5 à 5 cm/an. Cet effet du changement global (Takagi et al, 2016) 30 vient s'ajouter à la transgression marine due à la dilatation ther mique de la Mer de Chine (changement climatique) à un rythme sept fois supérieur.…”
Section: La Subsidence Accélérée Du Delta Du Mékongunclassified
“…Average subsidence rates for the Mekong delta were determined at 6 mm yr −1 from 1987–2006 by surface water level trend analysis (Fujihara et al 2015), 17.1 mm yr −1 from 1993–2013 for Can Tho city ( Takagi et al 2016 ) and 16 mm yr −1 from 2006–2010 at 15 monitoring stations by InSAR (Interferometric Synthetic Aperture Radar) ( Erban et al 2014 ). For Ho Chi Minh City (HCMC) local extreme rates of 46 mm yr −1 ( Erban et al 2014 ), and 70 mm yr −1 ( Minh et al 2015 ) are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some small island communities in the Philippines were subjected to frequent coastal flooding due to a sudden land subsidence triggered by the Bohol earthquake in 2013 [13]. Intense groundwater use, as well as natural consolidation, accelerated the rate of the subsidence in the Chao Phraya Delta, Thailand, and the Mekong Delta, Vietnam, which reached 5-15 cm/year and 2 cm/year, respectively [14,15]. On the other hand, the sediment accretion in mangrove forests is relatively slow, with a rate of several mm/year [16,17].…”
Section: Introductionmentioning
confidence: 99%